A Minireview on the Morpholine-Ring-Containing U.S. FDA Approved Drugs: A Medicinal-Chemistry-Based Analysis from 2013 to 2023 - Goel, Kapil Kumar; Singhal, Peeush; Sathish, Elagandhula; Babu, M. Arockia; Pandey, Sarvesh Kumar; Tyagi, Yogita; Kumar, Roshan; Singh, Thakur Gurjeet; Puri, Sarthak (Synlett, 2025)
Heterocyclic scaffolds, especially oxazines, constitute a significant component of clinically pertinent pharmaceuticals. Morpholine enhances the solubility, bioavailability, and metabolic stability of drug molecules because of its structural feature that gives optimum basicity (pKa = ca. 8.7), hydrogen bonding, and an electron-deficient ring system. Apart from structural features, incorporating morpholine ring systems in drug molecules improved their pharmacokinetic profiles also. It provides optimum lipid solubility as well as aqueous solubility. As a bioisosteric replacement unit for piperazine, piperidine, etc., the morpholine ring provides optimum basicity and lipophilicity. We have examined U.S. FDA approved small-molecule drugs (2012–2023) incorporating morpholine as core ring structures. The analysis identified 14 drugs approved in the past decade that contain morpholine ring systems, with 50% classified as anticancer agents. The CYP3A4 enzyme was identified as the main driver for the metabolism of these drugs, with the majority being excreted via feces. Three morpholine-containing drugs were identified as possessing chiral centers, taking into account stereochemical aspects. In addition to covering drugs with morpholine rings, the perspective offers a comprehensive analysis utilizing molecular descriptors, chemical space parameters, and commentary on these medications’ pharmacokinetic and pharmacodynamic aspects. This enhances the article’s medicinal chemistry dimension and renders it a valuable resource for the medicinal and allied science community.1 Introduction2 Insights towards the Chemistry of Morpholine3 Synthetic Strategies to Develop Morpholine Derivatives4 Implication of Morpholine in Improvising the Pharmacokinetics and Efficacy of Pharmaceutical Drugs: Case Studies5 Comparative Analysis of the Pharmacological Class of the Approved Drugs Possessing Morpholine System6 Delving Deeper into the Approved Drugs Bearing the Morpholine-Based Core Systems7 Analysis and Conclusion8 Summary
Keywords: heterocycles; morpholine; drug discovery; U.S. FDA approved; chemical space; molecular descriptors; chemical analysis; metabolism